Opinion - Barnard, Christian (Res Medica, 2014)
Organ transplantation has evoked such mixed and even violent reaction that it would seem worthwhile to explore the ethics governing it — and to do this by examining the three major areas of contention: the act itself, the recipient and the donor. IS TRANSPLANTATION ETHICAL? News coverage of transplantation in the popular mass media has been widespread, enthusiastic and, unfortunately, too often sensational and misleading. I t has been misconceived in certain sections of the public both as a panacea and as an unethical and unjustified form of treatment. Neither assertion is accurate. Within our currently limited understanding of immunological attack on an allograft and our inability to prevent such an onslaught, the transplantation of any organ must be accepted as palliative therapy — not a final cure. It achieves palliation which equals, if it does not surpass, some forms of palliation which have been accepted for many years as the only way to deal with malignant diseases. This being established, one cannot accept as unjustifiable or unethical the palliation of symptoms and extension of life itself.